2022
DOI: 10.3389/fcimb.2022.902428
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of autophagy as a therapeutic strategy for Toxoplasma gondii infection

Abstract: Toxoplasma gondii infection is a severe health threat that endangers billions of people worldwide. T. gondii utilizes the host cell membrane to form a parasitophorous vacuole (PV), thereby fully isolating itself from the host cell cytoplasm and making intracellular clearance difficult. PV can be targeted and destroyed by autophagy. Autophagic targeting results in T. gondii killing via the fusion of autophagosomes and lysosomes. However, T. gondii has developed many strategies to suppress autophagic targeting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 107 publications
1
9
0
Order By: Relevance
“…This fact may explain the lack of expression in LC3 transcription in THP-1 cell line infected by T. gondii RH strain. Our findings represented that T. gondii in THP-1 cell downregulated transcription of atg 12, while significant phosphorylation of rpS6 in protein level, in the line of previous studies, proposes deregulation of autophagy via mTORC manipulation by T. gondii [ 61 , 62 ]. However, our finding suggests that although immunosuppressant medications prescribed in IBD condition can increase the risk of opportunistic infection and likely re-activation of latent toxoplasmosis, T. gondii tachyzoites are not able to phosphorylate mTORC and inhibit autophagy during AZA treatment in IBD patients.…”
Section: Discussionsupporting
confidence: 92%
“…This fact may explain the lack of expression in LC3 transcription in THP-1 cell line infected by T. gondii RH strain. Our findings represented that T. gondii in THP-1 cell downregulated transcription of atg 12, while significant phosphorylation of rpS6 in protein level, in the line of previous studies, proposes deregulation of autophagy via mTORC manipulation by T. gondii [ 61 , 62 ]. However, our finding suggests that although immunosuppressant medications prescribed in IBD condition can increase the risk of opportunistic infection and likely re-activation of latent toxoplasmosis, T. gondii tachyzoites are not able to phosphorylate mTORC and inhibit autophagy during AZA treatment in IBD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Autophagy is a protective mechanism of eukaryotic cells against stress and infection. Autophagosome and lysosome can digest and degrade abnormal protein aggregation and damaged organelles, which is an adaptive response of most cells in many aspects ( Deretic et al., 2013 ; Cheng et al., 2022 ). In extracellular, T. gondii tachyzoites, autophagosomes are induced in response to amino acid starvation, but they can also be observed during normal intracellular development of the parasite ( Besteiro et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are four main types of autophagy: autophagosome-mediated macroautophagy, microautophagy, chaperone-mediated autophagy, and non-canonical autophagy ( 9 ). Macroautophagy (hereinafter referred to as autophagy) inhibits T. gondii infection through the formation of a PV-containing autophagosome and its fusion with the lysosome ( 11 ). In addition, the PV can also be targeted via autophagosome-independent processes orchestrated by autophagy proteins in IFN-γ-activated cells ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The host cell autophagic response against T. gondii is mainly triggered by CD40- and IFN-γ-dependent signals that induce the expression and activation of autophagy-related proteins (e.g., ULK1, Beclin-1, and LC3), a process that culminates with the destruction of the parasite by lysosomal enzymes ( 13 , 14 ). Accumulating evidence indicates that activation of the host serine/threonine kinase AKT constitutes one of the strategies developed by T. gondii to avoid autophagy-mediated killing ( 11 , 15 , 16 ). In this regard, it was reported that early and prolonged activation of EGF receptor (EGFR)-dependent AKT phosphorylation by T. gondii was required to prevent accumulation of autophagosome and lysosome components around the PV (i.e., LC3 and LAMP-1, respectively) and reduce parasite replication ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%